1973
DOI: 10.1063/1.1662197
|View full text |Cite
|
Sign up to set email alerts
|

Determining accurate superconducting tunneling energy gaps: Anisotropy in single-crystal Nb

Abstract: Superconducting tunneling experiments on niobium single crystals with indium and lead-bismuth counterelectrodes show an isotropic energy-gap value of 3.12±0.05 meV, or 3.93kTc, for 26 junction orientations. Self-consistent analysis criteria have been developed for the determination of gap values. These criteria are not met in the existing literature on transition-metal tunneling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…This gap is smaller than that measured on high quality Nb samples,   1.55 meV (Ref. [28] and figure 5(c)) and the coherence peaks are smeared, which is not surprising in view of the rather low TC of the pristine film (7.4 K). We note that molecules were not found within a few hundred nm from positions where such BCS-type spectra were measured, thus manifesting the localized nature of the chiral-induced OP modification.…”
Section: Figure 1: Topographic Images Of a Nb Film After Polyalanine ...mentioning
confidence: 55%
“…This gap is smaller than that measured on high quality Nb samples,   1.55 meV (Ref. [28] and figure 5(c)) and the coherence peaks are smeared, which is not surprising in view of the rather low TC of the pristine film (7.4 K). We note that molecules were not found within a few hundred nm from positions where such BCS-type spectra were measured, thus manifesting the localized nature of the chiral-induced OP modification.…”
Section: Figure 1: Topographic Images Of a Nb Film After Polyalanine ...mentioning
confidence: 55%
“…Electron tunnelling measurement of gap anisotropy in niobium has a long and unsettled history. In a careful study in 1973 Bostock et al [59] conducted tunnelling experiments on niobium single crystals in 26 directions, with carefully prepared indium and lead-bismuth counter-electrodes, only to detect no anisotropy, see TA-BLE V. This conclusion overrode earlier outcomes such as the 1967 MacVicar and Rose study [60] numerous directions and found gap values grouped nonrandomly in k-space. The final view was that there is no observed anisotropy.…”
Section: Niobiummentioning
confidence: 94%
“…This is a signature of the small gap anisotropy in Nb which agrees well with the prediction made in earlier calculations 24 as well as with experimental observations. [28][29][30][31] It is worthwhile noting that an increased temperature smearing (shown as the orange dashed line) of 1 K strongly suppresses the signature of the gap anisotropy in the DOS which may explain why no gap anisotropy is visible in the STM experiments of Ref. 33 that were done at 1.3 K.…”
Section: A Bulk Nbmentioning
confidence: 99%
“…It is a type-II s-wave superconductor with a fairly large critical temperature of T c ≈ 9.2 K and a large superconducting gap in the electronic structure of 2∆ ≈ 3 meV. Apart from experimental studies, [28][29][30][31][32][33] several ab initio electronic structure calculations are published that investigate the normal state properties [32][33][34][35] or directly calculate superconducting properties. 24,[36][37][38] This abundance of previously published data allows us to benchmark our implementation.…”
Section: Introductionmentioning
confidence: 99%